People’s Perspective towards Earthquake Risks and Its Mitigation Measures: In the Context of Rural Mountainous Region of Nepal - Singh, Ramesh Prasad; Praveen, B. M.; Shrestha, Diwat Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Nepal, located at the convergence of the Indian and Eurasian tectonic plates, is highly vulnerable to earthquakes due to active seismic zones formed by the ongoing continental collision, particularly along the Main Frontal Thrust. Historical records show frequent and devastating earthquakes, including the 2015 Gorkha quake that claimed around 9,000 lives and caused economic losses exceeding 6 billion. The western region, especially around Jajarkot, has not experienced a major earthquake in the past 2–3 decades, indicating significant seismic energy buildup and an increased risk of a high-magnitude event. Jajarkot district, a mountainous and rural area, is particularly at risk due to fragile geology, traditional construction methods, and poor access to disaster risk reduction (DRR) infrastructure. This study examines local perceptions of earthquake risk, drawing on recent events such as the 2015 Gorkha and 2023 Jajarkot earthquakes. It finds that while awareness exists, proactive mitigation is often limited by poverty, remoteness, and fatalistic cultural beliefs. However, these same cultural and religious systems, if integrated thoughtfully, offer potential platforms for community engagement and awareness. The study recommends adopting culturally sensitive education, strengthening community-based disaster preparedness, enhancing access to resilient construction materials, and decentralizing DRR initiatives. A territorially sensitive, people-centered approach is essential to improving earthquake resilience in Nepal’s rural highland regions.